2017
DOI: 10.1016/j.memsci.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Thin SAPO-34 membranes synthesized in stainless steel autoclaves for N2/CH4 separation

Abstract: SAPO-34 membranes were synthesized in stainless steel autoclaves and Teflon autoclaves with water bath, ice/water bath and flowing water cooling towards N 2 /CH 4 separation. The best membrane displaying unprecedented N 2 permeance of ~2,600 GPUs and N 2 /CH 4 separation selectivity of 7.4 was prepared in the stainless steel autoclave with a water bath cooling. A more selective membrane with a N 2 /CH 4 selectivity of 8.6 and N 2 permeance of ~2,150 GPUs was also prepared in the stainless steel autoclave but w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 42 publications
0
26
0
1
Order By: Relevance
“…Carreon、Yu 和 Funke 等 [35][36][37][38][39][40] 有着多年的研究经验, 成功制备出对轻质气体具有良好分离效果的 SAPO-34 膜, 国内的顾学红、张延风等 [41][42][43][44] [46] 。基于微波 加热法, Hu 等 [47] 制备出薄(厚度为 4 μm)且致密的 图 2 CHA 分子筛膜制备方法流程示意图 Fig. 2 Schematic diagrams of CHA zeolite membrane preparation methods [50][51] , 且其作为陶瓷材料与分子筛性质相似, 更易于膜层生长 [52] 。 针对 SSZ-13 膜, 周荣飞等 [27,31] 基于莫来石管合成了致密的 SSZ-13 膜, Kosinov 和 Lee 等 [14,[24][25] 基于管状、片状 α-氧化铝合成了性能 良好的 SSZ-13 膜。针对 SAPO-34 膜, 载体主要集 中在 α-氧化铝上, 如 Chen 和 Liu 等 [41,[53][54][55] [37,58] , 已有诸多文章报道了纳米 CHA 晶种的合 成方法 [59][60][61][62][63] , 亦有通过球磨方式将常见微米级 CHA 晶体研磨至纳米尺寸作为晶种, 虽所得晶种形状不 定, 但因仍保有 CHA 晶型而能够起到诱导合成的 作用。 Kosinov 等 [14] 将~10 μm SSZ-13 晶粒球磨得到 120 nm 的 晶 种 , 制 备 出 分 离 性 能 良 好 的 致 密 SSZ-13 膜; Huang 等 [40] 还发现使用大长径比的片状 [67] (图 3)。Bohström 等 [68] [14,24,[26][27] [41,53,66] , 后者基本在 170~190 ℃, 160 ℃下晶 化则会生成 AEI 沸石杂相 [69] 。 2)晶化时间。 晶化时间与 CHA 分子筛膜层的结 晶度与厚度密切相关, 通常要与晶化温度配合选取, 晶化时间过短会导致膜层不完整, 晶化时间过长会 使厚度过大(图 3)。 针对 SSZ-13 膜合成, 150~ 170 ℃ 下晶...…”
Section: 二次生长法unclassified
“…Carreon、Yu 和 Funke 等 [35][36][37][38][39][40] 有着多年的研究经验, 成功制备出对轻质气体具有良好分离效果的 SAPO-34 膜, 国内的顾学红、张延风等 [41][42][43][44] [46] 。基于微波 加热法, Hu 等 [47] 制备出薄(厚度为 4 μm)且致密的 图 2 CHA 分子筛膜制备方法流程示意图 Fig. 2 Schematic diagrams of CHA zeolite membrane preparation methods [50][51] , 且其作为陶瓷材料与分子筛性质相似, 更易于膜层生长 [52] 。 针对 SSZ-13 膜, 周荣飞等 [27,31] 基于莫来石管合成了致密的 SSZ-13 膜, Kosinov 和 Lee 等 [14,[24][25] 基于管状、片状 α-氧化铝合成了性能 良好的 SSZ-13 膜。针对 SAPO-34 膜, 载体主要集 中在 α-氧化铝上, 如 Chen 和 Liu 等 [41,[53][54][55] [37,58] , 已有诸多文章报道了纳米 CHA 晶种的合 成方法 [59][60][61][62][63] , 亦有通过球磨方式将常见微米级 CHA 晶体研磨至纳米尺寸作为晶种, 虽所得晶种形状不 定, 但因仍保有 CHA 晶型而能够起到诱导合成的 作用。 Kosinov 等 [14] 将~10 μm SSZ-13 晶粒球磨得到 120 nm 的 晶 种 , 制 备 出 分 离 性 能 良 好 的 致 密 SSZ-13 膜; Huang 等 [40] 还发现使用大长径比的片状 [67] (图 3)。Bohström 等 [68] [14,24,[26][27] [41,53,66] , 后者基本在 170~190 ℃, 160 ℃下晶 化则会生成 AEI 沸石杂相 [69] 。 2)晶化时间。 晶化时间与 CHA 分子筛膜层的结 晶度与厚度密切相关, 通常要与晶化温度配合选取, 晶化时间过短会导致膜层不完整, 晶化时间过长会 使厚度过大(图 3)。 针对 SSZ-13 膜合成, 150~ 170 ℃ 下晶...…”
Section: 二次生长法unclassified
“…22 In addition to studies aiming at the use of AlPOs/SAPOs in adsorption-based separations, some groups have also prepared AlPO or SAPO membranes for potential applications in separations of methane-containing mixtures. [24][25][26][27][28][29][30][31][32][33][34][35] These efforts have mainly addressed frameworks with eight-membered ring pore apertures, especially AEI-type AlPO-18 and CHA-type SAPO-34, because the diffusion of CO 2 or N 2 (kinetic diameters d kin of 3.30 Å and 3.64 Å, respectively 3 ) through these windows is faster than the diffusion of CH 4 (d kin = 3.80 Å). Since CO 2 is more strongly adsorbed than CH 4 , the combination of stronger adsorption and faster diffusion of carbon dioxide affords high CO 2 /CH 4 membrane selectivities: For example, Wang et al…”
Section: Introductionmentioning
confidence: 99%
“…were obtained for AlPO-18 and SAPO-34 membranes, respectively. 32,34,35 A preliminary economic assessment indicated that a membrane-based separation using SAPO-34 could be competitive to cryogenic distillation for small nitrogen-contaminated gas wells. 32 Computational studies using force-field based simulation methods have delivered valuable insights into the adsorption and diffusion of guest molecules in zeolites and related porous materials.…”
Section: Introductionmentioning
confidence: 99%
“…22 In addition to studies aiming at the use of AlPOs/SAPOs in adsorption-based separations, some groups have also prepared AlPO or SAPO membranes for potential applications in separations of methane-containing mixtures. [24][25][26][27][28][29][30][31][32][33][34][35] These efforts have mainly addressed frameworks with eight-membered ring pore apertures, especially AEI-type AlPO-18 and CHA-type SAPO-34, because the diffusion of CO 2 or N 2 (kinetic diameters d kin of 3.30 Å and 3.64 Å, respectively 3 ) through these windows is faster than the diffusion of CH 4 (d kin = 3.80 Å). Since CO 2 is more strongly adsorbed than CH 4 , the combination of stronger adsorption and faster diffusion of carbon dioxide affords high CO 2 /CH 4 membrane selectivities: For example, Wang et al…”
Section: Introductionmentioning
confidence: 99%